Hubungan Keaktifan Ekstrakurikuler Pendidikan Keperamukaan Dengan Sikap Disiplin Siswa Kelas Tinggi SDN 36 Kota Bengkulu - Rika Marlina; Lukman Lukman (JURIDIKDAS, 2020)
This study aims to determine the relationship between the activeness of students following extracurricular scouting education with student discipline attitudes. This research is quantitative research. The research method used is the correlation with the type of product moment design. The population in this study were all high-class students who took extracurricular scouting education. Sampling using random sampling but the sample in this study the entire population because it is less than 100 then the entire population is sampled with a total of 57. The research instrument used was a questionnaire sheet. Prerequisite test data analysis using tests of normality, homogeneity and hypothesis. This technique is used to determine the significant relationship between independent and dependent variables by comparing r_calculations and r_tabels with a significant level of 5%. Based on the results of data analysis, the value of r_calculations= 0.66>  r_tabels= 0.266, which means that there is a significant relationship between activeness in scouting extracurricular education and disciplinary attitude. Furthermore, the significance test results obtained t_calculations = 6.8 ? t_tabels= 1.67303 means that there is a significant relationship between variables for the entire population with a contribution of 43.56% between the activities of joining extracurricular scouting education with student discipline attitude. It was concluded that Ha was accepted where there was a relationship between the activities of joining the scouting extracurricular education with the discipline attitude of high class students at 36 Primary Schools in Bengkulu City.